DRYING KINETICS OF NIGER SEEDS - Silva,Fernanda P. Da (2017)
ABSTRACT: The objectives of this study were to describe the process of drying niger seeds through the fitting of different mathematical models to the experimental drying data, to select the best model that represents the phenomenon, and to determine the diffusion coefficients and thermodynamic properties of the product. Seeds with an initial moisture content of 0.42 (d.b) were collected and dried at 40°, 50°, 60°, 70°, and 80°C in a fixed bed experimental dryer. After drying, different mathematical models were fitted to determine the diffusion coefficient by applying liquid diffusion theory, which allowed for calculation of the energy activation, enthalpy, entropy, and Gibbs free energy values. The Page model was selected to represent the drying process of niger seed drying, as it is a traditional and simple model. The effective diffusion coefficient increased as the temperature increased. The activation energy for liquid diffusion at the temperature range of 40°C to 80°C was 46.83 kJ mol−1. The enthalpy and entropy specific values decreased as the drying air temperature increased. The Gibbs free energy values also increased as the drying air temperature increased.